DESAIN GEOMETRI PERSIMPANGAN DAN AKSES KAMPUS UNIVERSITAS KRISTEN PETRA - Setiawan, Rudy (Jurnal Transportasi, 2012)
Congestion that occurred in the vicinity of Petra Christian University campus tends to increasing on the peak hours. One of the possible solutions to reduce congestion is to revamp the geometric design of campus access, as proposed in the final report of PCU Master Plan. The study was conducted to determine differences in the intersection performance indicator between the existing conditions compared with the proposed access design. The data was collected through survey of road inventory, origin-destination, and turning movement. The traffic assignment process carried using Trafikplan software, and analysis of the access performed by using software KAJI. Based on the result, it can be inferred if the proposed design ofgeometric access implemented, the intersection capacity estimated to be increase up to 46.6%, degree of saturation reduce up to 31.9%, intersection delay reduce up to 57%, and queue probability reduce up to 50.9%; compared with the existing access conditions till the year 2020. The demand management program should also be considered as an option to reduce congestion.Keywords: unsignalised intersection, reversible lane